Tristetraprolin limits age-related expansion of myeloid-derived suppressor cells - Kwack, Kyu Hwan; Zhang, Lixia; Kramer, Elliot D.; Thiyagarajan, Ramkumar; Lamb, Natalie A.; Arao, Yukitomo; Bard, Jonathan E.; Seldeen, Kenneth L.; Troen, Bruce R.; Blackshear, Perry J.; Abrams, Scott I.; Kirkwood, Keith L. (Frontiers in Immunology, 2022)
Aging results in enhanced myelopoiesis, which is associated with an increased prevalence of myeloid leukemias and the production of myeloid-derived suppressor cells (MDSCs). Tristetraprolin (TTP) is an RNA binding protein that regulates immune-related cytokines and chemokines by destabilizing target mRNAs. As TTP expression is known to decrease with age in myeloid cells, we used TTP-deficient (TTPKO) mice to model aged mice to study TTP regulation in age-related myelopoiesis. Both TTPKO and myeloid-specific TTPKO (cTTPKO) mice had significant increases in both MDSC subpopulations M-MDSCs (CD11b+Ly6ChiLy6G-) and PMN-MDSCs (CD11b+Ly6CloLy6G+), as well as macrophages (CD11b+F4/80+) in the spleen and mesenteric lymph nodes; however, no quantitative changes in MDSCs were observed in the bone marrow. In contrast, gain-of-function TTP knock-in (TTPKI) mice had no change in MDSCs compared with control mice. Within the bone marrow, total granulocyte-monocyte progenitors (GMPs) and monocyte progenitors (MPs), direct antecedents of M-MDSCs, were significantly increased in both cTTPKO and TTPKO mice, but granulocyte progenitors (GPs) were significantly increased only in TTPKO mice. Transcriptomic analysis of the bone marrow myeloid cell populations revealed that the expression of CC chemokine receptor 2 (CCR2), which plays a key role in monocyte mobilization to inflammatory sites, was dramatically increased in both cTTPKO and TTPKO mice. Concurrently, the concentration of CC chemokine ligand 2 (CCL2), a major ligand of CCR2, was high in the serum of cTTPKO and TTPKO mice, suggesting that TTP impacts the mobilization of M-MDSCs from the bone marrow to inflammatory sites during aging via regulation of the CCR2-CCL2 axis. Collectively, these studies demonstrate a previously unrecognized role for TTP in regulating age-associated myelopoiesis through the expansion of specific myeloid progenitors and M-MDSCs and their recruitment to sites of injury, inflammation, or other pathologic perturbations.